Adaptability to Green Building Regulations in Oil-Producing Countries: Obstacles and Solutions - Alshamsi, Hamda Obaid; Alshehhi, Maitha Abdullah; Sakhrieh, Ahmad (International Journal of Energy Economics and Policy, 2022)
The sustainable building approach in the United Arab Emirates (UAE) has encountered impediments, as it is a new practice for society in UAE. Here, traditional construction methods are still adopted without considering environmental issues and growing concern over climate change. To overcome these problems, the Ras Al Khaimah Municipality launched new green building regulations called Barjeel in 2018. It is set to reduce 30% of energy and water consumption for new buildings. Based on the survey and interview results from 38 residents, consultants, and contractors, this study aims to identify the adaptability of Barjeel and the reasons behind the denunciation of these new regulations, and ultimately proposing some solutions to overcome the barriers. The findings from this study reveal that the surveyed population is aware of the concepts of green building practice but are also cognizant of the constraints that prevent its application such as high costs, availability of green and sustainable materials as well as expert personnel and skilled labour. Additionally, there are valid technical constraints and supply chain issues that should be addressed so that the basic infrastructure required to establish green building practices and help them flourish is in place and can be used for widespread green and sustainable building in the UAE